Analisis Studi Kasus terhadap Dampak Anak Broken Home pada Kesehatan Mental dan Pembelajaran : Study Analysis of the Impact of Broken Home Conditions on Mental Health and Learning - A. Fawziyyah; M. Amirullah (Litera Academica Publishing, 2025)
The increasing number of broken home cases among adolescents has become an urgent social issue due to its serious impact on mental health and academic learning. This study aims to describe the effects of a broken home condition on the mental well-being and learning process of a female adolescent in Makassar, using a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation involving a high school student whose parents are separated, as well as supporting informants including a guidance counselor and a close friend. The data were analyzed through thematic analysis consisting of data reduction, data presentation, conclusion drawing, and validation through member checking and source triangulation. The findings indicate four major results: (1) the broken home situation triggers emotional distress such as anxiety, deep sadness, loss of motivation, and behavioral changes; (2) cognitive functions such as concentration and memory are disrupted, which negatively affects academic achievement; (3) social withdrawal and difficulty building interactions at school emerge as adaptive responses; and (4) social support from teachers, peers, and school counselors plays a crucial role in emotional recovery. The study concludes that the broken home condition significantly influences adolescents’ mental health and learning process, with implications for schools to strengthen responsive counseling services and enhance collaboration with parents to ensure continuous support. Keywords: Broken Home; Mental Health; Learning; Adolescents.